The impact of left atrial strain parameters on systolic and diastolic improvement following TAVI. (14th October 2021) - Vattay, B; Nagy, A I; Apor, A; Kolossvary, M; Manouras, A; Molnar, L; Vecsey-Nagy, M; Boussoussou, M; Bartykowszki, A; Jermendy, A L; Zsarnoczay, E; Maurovich-Horvat, P; et al.
Abstract: Introduction: Transcatheter aortic valve implantation (TAVI) can improve left ventricular (LV) mechanics and has been shown to improve long term survival. Data on the prognostic value of left atrial (LA) strain following TAVI are scarce. LA strain – a surrogate of LV filling pressure - can aid the early detection of diastolic dysfunction and correlates with the extent of fibrosis in atrial remodelling. Purpose: In this multimodality study, we aimed to evaluate the prognostic value of LA function measured before hospital discharge following TAVI and to further elucidate its association with LV and LA reverse remodelling. Methods: In this prospective single center study, we investigated 90 patients (mean age 78.5 years, 46.7% female) with severe, symptomatic aortic stenosis (AS) who underwent transthoracic echocardiography immediately after TAVI and 6 months later. LA and LV global longitudinal strain parameters were obtained by speckle tracking echocardiography. CT angiography (CTA) was performed for pre-TAVI planning and repeated at 6 months follow-up. LV mass values were derived from the serial CTA images. We defined LV reverse remodelling as reduction of myocardial mass quantified on CTA and as an improvement of LV global longitudinal strain (GLS). LA reverse remodelling was assessed based on the peak reservoir strain values (LAGS). The association of LA and LV global strain parameters, LA stiffness, systolic and diastolic functional parameters and LV mass based reverse remodelling were analysed using Pearson correlation coefficient and linear regression models. Results: The mean LAGS and LVGLS values were 17.7% and 15.3% at discharge and 20.2% and 16.6% at follow-up, respectively (p=0.024, p<0.001). LA and LV strain values improved in 60.6% and 74.5% of all patients. Reduced LAGS (<20%) was found in 66.7% of all patients at baseline. LA strain at discharge correlated significantly with diastolic parameters (E wave, E/e', LAVI, all p<0.05). Atrial reverse remodelling based on LAGS change correlated with LVGLS change (p<0.01, standardized β=0.53) and LAGS at discharge (p=0.012, standardized β=−0.30). LAGS correlated with the extent of morphological LV remodelling based on LV mass reduction (p=0.002, coeff: 0.36). Elevated LA stiffness at discharge (upper tercile) leads to substantially lower LAGS at 6 months versus patients with lower LA stiffness value (1. and 2. tercile): 16.4±10.0 vs 21.9±9.8, p=0.042. Conclusion: Patients with reduced LAGS immediately after TAVI showed a larger extent of LV reverse remodelling during follow up. On the other hand, increased LA stiffness at discharge was consistent with irreversible LA damage as demonstrated by a lack of improvement in LA function. Funding Acknowledgement: Type of funding sources: None.